Analysing Learning Material For Young Learners Through The Framework - Afnesha Noveriana Chang (Jurnal Ilmiah Langue and Parole, 2023)
Nowadays, Indonesian kids are increasingly interested in bilingual education. They are exposed to the second language in their households in addition to acquiring it in school. Although there are still some myths about bilingualism in society, some parents still practice it because they think it helps their children develop, both linguistically and cognitively. Those, this essay focuses on the materials used by parents and teachers to teach bilinguals to the children including in the formal language learning. The literature review specifically served as the foundation for this paper. Here, seven frameworks about the learning materials are analysed to see whether the current materials are suitable for the students need. The results show that the learning materials still need some improvement and teachers need to do some innovation to make it happen the school level.